2010
DOI: 10.1167/iovs.09-4959
|View full text |Cite
|
Sign up to set email alerts
|

GITR Ligand–Mediated Local Expansion of Regulatory T Cells and Immune Privilege of Corneal Allografts

Abstract: Presence of Foxp3+CD25+CD4(+) Treg in the allograft is necessary for allograft survival. GITRL-dependent expansion of Treg within the cornea is one mechanism underlying immune privilege in corneal allografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 49 publications
2
44
0
6
Order By: Relevance
“…Additionally, because blockade of PD-1 ligands only partially reduced the ability of rapa-ECs to preferentially activate Tregs, it is likely that there are other mechanisms behind this observation. Although ligation of GITR on Tregs by GITR ligand was initially thought to abrogate their suppressive activity (78), recent studies suggest that GITR ligand may act to maintain and expand Tregs (79)(80)(81). Additionally, the interaction between OX40 and OX40 ligand has been shown to be important in Treg cell development in the gut (82), and an OX40 agonist enhanced Treg proliferation (83).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, because blockade of PD-1 ligands only partially reduced the ability of rapa-ECs to preferentially activate Tregs, it is likely that there are other mechanisms behind this observation. Although ligation of GITR on Tregs by GITR ligand was initially thought to abrogate their suppressive activity (78), recent studies suggest that GITR ligand may act to maintain and expand Tregs (79)(80)(81). Additionally, the interaction between OX40 and OX40 ligand has been shown to be important in Treg cell development in the gut (82), and an OX40 agonist enhanced Treg proliferation (83).…”
Section: Discussionmentioning
confidence: 99%
“…A third possibility is that allo-activated T-cells were being restrained by active immunoregulatory mechanisms and/or the inherent immune regulatory environment of the anterior chamber of the eye. The involvement of Foxp3 þ regulatory T-cells in graft acceptance has been documented in mice, 32 and availability of antibodies specific for both swine CD25, 33 and Foxp3 34 permit this to be investigated in pigs in future.…”
Section: Discussionmentioning
confidence: 99%
“…44 We have also found that constitutive expression of glucocorticoid-induced tumor necrosis factor receptor familyrelated protein ligand in the cornea mediates local expansion of CD25 + CD4 + T regulatory cells in the cornea and suppresses conventional effector T-cell function. 45 Thus, corneal tissue has a self-regulation system for preventing inflammationmediated corneal tissue destruction, using differently functioning molecules. These immune suppressive molecules are mainly expressed on corneal endothelial cells.…”
Section: Discussionmentioning
confidence: 99%